Arus Utama Perdebatan Hukum Perkawinan Beda Agama - Khamami Zada (AHKAM : Jurnal Ilmu Syariah, 2013)
Abstract: Mapping the Mainstreaming Debate Regarding to Interfaith Marriage Law. This article intends to observe the linkage of the implementation of interfaith marriage law  with the opinion of  Islamic jurists’ and to political and social change in a country. Interfaith marriage law—as occurred in (former) North Yemen, Jordan, Algeria, and Iraq—is not influenced by the Islamic school of thought of the majority population. In contrary, interfaith marriage in the aforementioned states is not inline with the mainstream opinion of islamic jurists that forbidding softly (makrūh) Muslim man to marry a woman of Ahl al-Kitāb. The regulation is obviously influenced by  the rise of Islamism, such as the Muslim brotherhood in Jordan, Front Islamic Salvation in Algeria, and the growing influence of Shiite movements in Iraq and North Yemen in establishing religious conservatism in matters of interfaith marriage. Thus, it can be understood why those countries prefer to refer  text of the Quran that regulate interfaith marriage law.Keywords: interfaith marriage law, islamic family law, Ahl al-KitābAbstrak: Arus Utama Perdebatan Hukum Perkawinan Beda Agama. Artikel ini ingin menguji keterhubungan pemberlakuan hukum perkawinan beda agama dengan pendapat-pendapat ulama fikih dan perubahan sosial politik suatu negara. Hukum perkawinan beda agama di Yaman Utara, Yordania, Aljazair, dan Irak tidak begitu sepenuhnya dipengaruhi oleh mazhab fikih yang dianut mayoritas penduduknya. Justru perkawinan beda agama di negara-negara tersebut sedikit keluar dari mainstream pendapat ulama fikih yang memakruhkan laki-laki Muslim yang menikah dengan wanita Ahl al-Kitāb. Posisi ini diambil bukan karena dipengaruhi oleh kolonialisme Barat yang berlangsung lama dalam memberlakukan hukum, melainkan kuatnya Islamisme, seperti Ikhwanul Muslimin di Yordania, Front Islamic Salvation di Aljazair, dan kuatnya pengaruh gerakan Syiah di Irak dan Yaman Utara dalam membangun konservatisme agama dalam urusan perkawinan beda agama. Tidak heran jika empat negara ini mengambil jalan kembali ke teks Alquran untuk mengatur hukum perkawinan beda agama.Kata Kunci: hukum perkawinan beda agama, hukum keluarga Islam, Ahl al-Kitāb